For a transforming education: a nursing teaching experience - Bezera, Maria Gorette Andrade; Gurgel, Almerinda Holanda; Fernandes, Ana Fátima Carvalho (Rev Rene, 2006)
This is a descriptive study that aimed at learning about the students’ view of the teaching and practice theory, developed in accordance with the DHEG thematic. The teaching experience consisted of lessons given to 42 students of the sixth semester, of the Nursery Academic Course of a private university in Fortaleza-Ce. The academic subject was Gynecology and Obstetrics focusing on the thematic "hypertensive disease specific of pregnancy and the nursing care". The research was accomplished with the participation of 42 students. The data collection was done through the participative observation and through a semi-structured questionnaire containing data which referred to the approached contents, the teaching strategy and the relationship teacher/student. The data analysis was done by reading the depositions, relating them to the participative observation, which revealed the pertinence of the contents, in which were considered current aspects. The teaching strategies favored the student to relate theory to practice and the fact that the relationship teacher/student was based on dialogue. It was concluded that the use of strategies which make the student become interested in research, and in participating in the classes through the dialogue, favors learning.